2006
DOI: 10.1124/jpet.106.110247
|View full text |Cite
|
Sign up to set email alerts
|

Modest Inflammation Enhances Diclofenac Hepatotoxicity in Rats: Role of Neutrophils and Bacterial Translocation

Abstract: Idiosyncratic adverse drug reactions (IADRs) represent an important human health problem, yet animal models for preclinical prediction of these reactions are lacking. Recent evidence in animals suggests that some IADRs arise from drug interaction with an inflammatory episode that renders the liver sensitive to injury. Diclofenac (DCLF) is one of those drugs for which the clinical use is limited by idiosyncratic liver injury. We tested the hypothesis that modest inflammation triggered in rats by a small dose of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
96
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(103 citation statements)
references
References 31 publications
6
96
0
1
Order By: Relevance
“…On the other hand, the pathogenic role of other inflammatory cells such as neutrophils in the drug-inflammation interaction model is also mentioned in previous investigations. 23,50 Hence, neutrophils and other immune cells might also be responsible for the liver injury induced by AQ and CQ. Inhibition of these cells (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, the pathogenic role of other inflammatory cells such as neutrophils in the drug-inflammation interaction model is also mentioned in previous investigations. 23,50 Hence, neutrophils and other immune cells might also be responsible for the liver injury induced by AQ and CQ. Inhibition of these cells (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigations indicated that the threshold for hepatotoxicity from many xenobiotics was lowered by co-exposure to LPS. 22,23,[40][41][42][43] The ability of LPS to stimulate an inflammatory response may account for its pathogenicity in the liver. LPS is a potent activator of liver tissue macrophages (Kupffer cells) through toll-like receptors (TLRs) (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This hypothesis is supported by the observation that neutrophil depletion protects against paracetamol toxicity [67] . Also, idiosyncratic reactions are more likely to occur in the presence of an inflammatory state [68] . Effectors are dendritic cells, which act by sensing pathogens and triggering adaptive immune responses.…”
Section: Immune Systemmentioning
confidence: 99%
“…Based on this possible mechanism, there are some in vivo non-clinical animal models designed for the estimation of the idiosyncratic DILI. Lipopolysaccharide (LPS) co-treated rats have been reported to be one of the in vivo models to estimate the potential of idiosyncratic DILI for some drugs, including chlorpromazine (Buchweitz et al, 2002), diclofenac (Deng et al, 2006), ranitidine (Luyendyk et al, 2003), sulindac (Zou et al, 2009) and trovafloxacin . However, the utility of this model for the estimation of idiosyncratic DILI remains controversial because treatment with LPS intentionally destroys the immune system in normal rats.…”
Section: Introductionmentioning
confidence: 99%